Effects of Budget Target Clarity, Internal Control, and Reporting Systems on OPD Accountability Moderated Culture - Putri Ayu Lestari; Rina Br Bukit; Ibnu Austrindanney Sina Azhar (International Forum of Researchers and Lecturers, 2026)
The purpose of this study is to examine and analyze whether budget target clarity, internal control, and reporting system affect performance accountability with organizational culture as a moderating variable in Regional Government Organizations (OPD) of Langsa City.This study was conducted on 24 Regional Government Organizations of Langsa City. The sampling technique used total sampling with a population of 120 respondents occupying strategic positions. Hypothesis testing uses Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis through the SmartPLS 4.0 application. The results of this study indicate that budget target clarity has no effect on performance accountability, while internal control has a positive and significant effect on performance accountability. The reporting system has no effect on performance accountability. Organizational culture is able to moderate and strengthen the effect of budget target clarity on performance accountability. Organizational culture moderates the effect of internal control on performance accountability, but in a weakening direction. Organizational culture is unable to moderate the effect of the reporting system on performance accountability.